Green Infrastructure as an Urban Landscape Strategy for the Revaluation of the Ite Wetlands in Tacna - Vanessa Raymundo; Carlos Vargas; Claudia Alcalá; Silvana Marin; Clarisse Jaulis; Doris Esenarro; Elias Huerta; Diego Fernandez; Pedro Martinez (Buildings)
This study is focused on proposing a green infrastructure design that revalues the Ite Wetlands in Tacna. Currently, the Ite Wetlands are experiencing significant degradation mainly due to water pollution in the wetland and other associated environmental and social impacts. This situation is exacerbated by nearby mining activity, which includes the discharge of mining tailings that negatively affect water quality and the surrounding natural environment. An exhaustive diagnosis was conducted, considering multiple urban and environmental aspects, such as topography, road networks, climatic conditions, and biological diversity. The green infrastructure and revaluation project for the Ite Wetlands in Tacna has generated significant results, highlighted by the careful design of green corridors. The implementation of interpretive trails, rest areas, birdwatching viewpoints, and botanical gardens has transformed the wetlands into a multifunctional environment that promotes environmental conservation and biodiversity. This initiative has not only revitalized the area but strengthened the cultural and social identity of the region. The proposal provides a sustainable development model that can serve as inspiration for other natural areas facing degradation.